Penyesuaian Diri Siswa Sekolah Berasrama (Studi Deskriptif Komparatif Terhadap Siswa SMAN 1 Sumatera Barat) - Peni Okto Randi (Medan State University, 2021)
Self adjustment of students in a boarding school environment is the ability to live and fair, so that he was satisfied with themself and to the environment. Many factors affect the students in the school adjustment as gender, cultural backgrounds and grade levels (maturity). This study purpose to describe the adjustment of students in terms of gender, cultural background, and grade levels. The research was ex post facto by using factorial design 2 x 2 x 3. The population is students of SMAN 1 West Sumatra. The total sample were 168 people selected by stratified random sampling technique and combined with the proportional sampling technique. The instrument was a questionnaire. Data were analyzed by analysis of variance (ANOVA). The result showed: (1) the level of adjustment of students in general were in the high category, (2) the level of adjustment male and female were in at the high category, and there was difference of adjustment of students based on the gender, mean score of female students higher than male students, (3) the level of adjustment of students in terms of cultural background (Minang and non-Minang) were in high category, and there are differences in the adjustment of students based on the background of the culture, (4) the level of adjustment student review grade levels (X, XI, and XII) were in high category, and there is no difference adjustment students based on grade level, and (5) the level of adjustment of students in terms of gender, cultural background, and grade levels were in category high, and there is no interaction between these variables in explained the adjustment of students.